Identifikasi Faktor Keikutsertaan Akseptor Tubektomi Kota Surabaya di klinik PKBI Jawa Timur - Lidia Grestanti; Nurul Fitriyah (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2018)
Tubectomy is one of  the family planning method in Indonesia. Family Planning service can be performed in many health services. One of them is in Planned Parenthood Federation of Indonesia (PPFI) clinic. According to Indonesian Health Ministry data (2013) reported that the coverage of Tubectomy method only 1.52%. The effectivity of Tubectomy is 99%. Many benefit from using Tubectomy method but its coverage in Indonesia is low. The purpose of research is to identify participation factors of Tubectomy acceptor in Surabaya on PPFI clinic. Design of this research is using descriptive research method. The population of this research is woman that do Tubectomy in PPFI clinic of East Java on September 2017. There are 46 peoples for this research population. Sampling technic is population total. Variables are sociodemography factor, such as age, education, last child age, alive children and health factor which is contraception method and blood pressure. Result analized using descriptive statistic. The result showed that sociodemography factor in Tubectomy acceptor with high result were age that pass childbearing age (35–39 year) is 41%, education level in Senior High School (52%), having 3–4 children (57%), their last child age is 0–5 years old (74%).Many woman in Hypertension level I their last family planning method was injection 8 peoples in total.